Do Clinical Ethicists Improve with Experience? And, If So, How Would We Know? - Seavilleklein, Victoria; Flynn, Jennifer; Frolic, Andrea; Wagner, Frank; Lee-Ameduri, Katarina (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2024)
During our workshop at the 2023 CBS-SCB Workshop and Community Forum, we explored and problematized the concept of “improvement” of clinical ethicists, situated within the larger context of discussions about the professionalization of clinical ethics. This summary provides key insights on this topic by clinical ethicists from across Canada and includes suggestions for steps that we might want to take in the field to enable and support the improvement of clinical ethicists going forward.